Development of gifted children in the art educational enviroment - Dobrovolska, Rufina; Gazinska, Olesya (Social work and education, 2022)
Solving a wide range of methodological and applied problems related to the reproduction and capacity building of gifted children and youth requires the creation of an artistic educational environment as a set of conditions for learning, development, individualization and socialization of gifted individuals. giftedness in accordance with natural inclinations, interests, requirements of age socialization, on the one hand, and social demand, on the other. Despite the existing research in psychology and pedagogy on the problem of the educational environment, the only position on the definition of "artistic educational environment", the structure and methods of its creation, is still under development. One of the reasons for this is the variety of methodological prerequisites and empirical principles for research on the problem of artistic educational environment for the gifted. Overcoming methodological and methodological differences is possible only if we take into account psychological features, patterns and principles of gifted personality as a starting point for creating educational systems and technologies (unity of goals, content, methods and learning conditions), including artistic educational environment as a condition for their practical implementation. The use of innovative technologies does not always meet the specifics of the phenomenon of giftedness and individual psychological characteristics of gifted children and youth, and therefore does not give the desired result for full disclosure of the potential of gifted at different stages of age. The reasons for these difficulties and ways to overcome them are not yet fully understood, and therefore should be the subject of theoretical and methodological reflection and empirical research. Thus, the trend towards personality-oriented and culturally appropriate educational systems and technologies necessarily requires the design and creation of this type of educational environment for gifted children, whose integrative quality indicator is the ability to provide all actors in the educational process a system of opportunities for effective personal self-development. That is why there is a problem of creating favorable conditions for the development of creative, intellectual and spiritual potential of gifted children in the context of the system "man - environment", in accordance with natural inclinations, interests, needs, age requirements, on the one hand, and social request, on the other. Thus, the logic of the development of pedagogical science requires special psychological research to determine the structure and principles of building an artistic educational environment focused on the manifestation, development and full realization of gifted children.